If it's not what You are looking for type in the equation solver your own equation and let us solve it.
10(6x-2)=+4(12x+6)
We simplify the equation to the form, which is simple to understand
10(6x-2)=+4(12x+6)
Reorder the terms in parentheses
+(+60x-20)=+4*(12x+6)
Remove unnecessary parentheses
+60x-20=+4+*(+12x+6+)
Reorder the terms in parentheses
+60x-20=+(+48x+24)
Remove unnecessary parentheses
+60x-20=+48x+24
We move all terms containing x to the left and all other terms to the right.
+60x-48x=+24+20
We simplify left and right side of the equation.
+12x=+44
We divide both sides of the equation by 12 to get x.
x=3.6666666666667
| s^2-19s+88=0 | | (2x+5)+(5x-7)=18 | | 1/4x=1/4x | | 6=-5a+4a | | 31-4(2x+11)=19 | | 3+3x+3=x-1 | | .74(x-12)=12 | | b-4=-4-4b | | 2m+6+4m=-6 | | ln(2x+1)(x+2)=2ln(x+2) | | 11x-2(3x+7)=6 | | -10d=4 | | 4x-4/5x=64 | | 2x^2/7*3/4x^2 | | 10x-3=45x+4 | | w^2-11w-110=-110 | | -15=-6m-3+2m | | X^2-33x-240=0 | | -2-10x=-2x+6 | | -6x-2-3=-17 | | 10x-3=45x+5 | | n/11=-9 | | 45i-27/-18 | | -9(3x+11)+7(12x-3)=2x-5x | | -3r=-6 | | x-7.3=2.5 | | x/17=19 | | (x^2/3y^3)^3 | | r^2+8r-24=-24 | | 3-8/6i | | r+9=-6 | | -xover-1=2 |